Microbiota alterations in patients treated for susceptible or drug-resistant TB - M. Hauptmann; B. Kalsdorf; J.E. Akoh-Arrey; C. Lange; U.E. Schaible (IJTLD Open)
BACKGROUND: We investigated alterations of human microbiota under anti-TB therapies in relationship to the level of Mycobacterium tuberculosis drug response. METHODS: Stool, sputum, and oral swab samples were analysed from participants with treatment-naïve TB and participants treated for drug-susceptible TB (DS-TB), drug-resistant TB without injectable drugs (DR-TB-inj–), or with injectable drugs (DR-TB-inj+) at 27–42 days of therapy. RESULTS: From September 2018 to December 2019, 5 participants with treatment-naïve TB, 6 participants with DS-TB, 10 participants with DR-TB-inj–, and 4 participants with DR-TB-inj+ were recruited. Reduced alpha diversities in stool samples indicated more profound dysbiosis in participants treated for DR-TB than in participants treated for DS-TB (–12% (non-significant) for DS-TB, –44% (P < 0.001) for DR-TB-inj–, and –60% (P < 0.05) for DR-TB-inj+ compared to treatment-naïve participants). While reduced abundances were observed in numerous taxa, genus Lactobacillus revealed the most substantial abundance increase in sputa of participants treated for DR-TB compared to treatment-naïve ones (P < 0.05 for DR-TB-inj– and DR-TB-inj+). Notably, a group of nosocomial pneumonia-associated taxa was increased in oral swabs of the DR-TB-inj+ compared to the treatment-naïve group (P < 0.05). CONCLUSIONS: Second-line anti-TB therapy in participants with DR-TB results in altered microbiota, including reduced alpha diversity and expansion of phylogenetically diverse taxa, including pathobionts.